Study on Deformation and Failure Characteristics of Surrounding Rock of Overlying Roadway under Upward Mining in the Deep Mine - Teng-Gen Xiong; Ju-Cai Chang; Kai He; Ya-Feng Su; Chao Qi (Geofluids)
To study the impact of mining of the lower protective layer on the deformation and failure characteristics of the upper roadway, these characteristics of an 879 gas drainage roadway were studied and analyzed during the mining of the II 1051 working face of the Zhuxianzhuang coal mine using similar simulation experiments and numerical simulation methods. The results indicate that with the continuous excavation of the working face, the range of impact of the mining stress gradually spreads and exceeds the level of the roadway. At the present time, the roadway is in a mining stress-rising area. The two sides of the roadway are sheared, and the roof and floor are under tension–shear composite failure. The floor is the most gravely damaged—the depth of its damage is 2.5 m, and the depths of damage on either side and of the roof are approximately 1–2 m. During the advancing process of the working face, the deformation of the roadway increases slowly at first, then increases sharply, and tends to be stable thereafter. The deformation of the floor is the largest, followed by those of the two sides and the roof; the values are 800, 400, and 300 mm, respectively.